Physical Activity and Knee Joint Injuries - Risk Factors, Management and Prognosis - Falkowski, Wojciech; Gaszyńska, Monika; Drzewiecka, Antonina; Drzewiecki, Artur; Korczak, Wiktor; Madejska, Maria; Rudzka, Aleksandra; Krysińska, Anna; Woźniak, Weronika; Magielski, Jakub (Journal of Education, Health and Sport, 2025)
Introduction and Aim: Physical activity is one of the main risk factors for knee joint injuries, and the risk depends on the specific sport. Each part of the knee joint can be at different risk of injury. Diagnosis, treatment and rehabilitation are key to returning to full mobility, but vary depending on the type of injury. The purpose of this article is to present risk factors, diagnosis, treatment and prognosis in the most common knee joint injuries. Review Methods: 35 studies from PubMed and Google Scholar were analyzed to examine the relationship between physical activity and knee joint injuries. Joint anatomy, diagnosis, treatment and rehabilitation in the context of amateur and professional sports were considered. State of Knowledge: Knee joint injuries often result from sudden movements. ACL rupture is the most common injury, often non-contact. Diagnosis is based on history and imaging studies, such as magnetic resonance imaging (MRI) to evaluate soft structures and X-rays for bone injuries. Treatment depends on the type of injury: in mild cases rehabilitation is sufficient, in more serious cases surgery. Summary: Physical activity is a major risk factor for knee injuries, and the most common injury is an ACL injury. The risk depends on the mechanism of injury, age, weight and previous injuries. It is crucial to take a history, do a physical examination and perform imaging to make a diagnosis. Proper diagnosis allows for the selection of the appropriate treatment and rehabilitation method, which affects the patient's prognosis and return to full physical activity.